NEK1 and DYNC2H1 are both involved in short rib polydactyly Majewski type but not in Beemer Langer cases. Issue 4 (12th April 2012) - El Hokayem, Joyce; Huber, Céline; Couvé, Adeline; Aziza, Jacqueline; Baujat, Geneviève; Bouvier, Raymonde; Cavalcanti, Denise P; Collins, Felicity A; Cordier, Marie-Pierre; Delezoide, Anne-Lise; Gonzales, Marie; Johnson, Diana; et al.
Abstract : Background: The lethal short rib polydactyly syndromes (SRP type I–IV) are characterised by notably short ribs, short limbs, polydactyly, multiple anomalies of major organs, and autosomal recessive mode of inheritance. Among them, SRP type II (Majewski; MIM 263520) is characterised by short ovoid tibiae or tibial agenesis and is radiographically closely related to SRP type IV (Beemer-Langer; MIM 269860) which is distinguished by bowed radii and ulnae and relatively well tubulated tibiae. NEK1 mutations have been recently identified in SRP type II. Double heterozygosity for mutations in both NEK1 and DYNC2H1 in one SRP type II case supported possible digenic diallelic inheritance. Methods: The aim of this study was to screen DYNC2H1 and NEK1 in 13 SRP type II cases and seven SRP type IV cases. It was not possible to screen DYNC2H1 in two patients due to insufficient amount of DNA. Results: The study identified homozygous NEK1 mutations in 5/13 SRP type II and compound heterozygous DYNC2H1 mutations in 4/12 cases. Finally, NEK1 and DYNC2H1 were excluded in 3/12 SRP type II and in all SRP type IV cases. The main difference between the mutation positive SRP type II group and the mutation negative SRP type II group was the presence of holoprosencephaly and polymycrogyria in the mutation negative group. Conclusion: This study confirms that NEK 1 is one gene causing SRP type II but also reports mutations in DYNC2H1, expanding the phenotypic spectrum of DYNC2H1 mutations. The exclusion of NEK1 and DYNC2H1 in 3/12 SRP type II and in all SRP type IV cases further support genetic heterogeneity.